A thermal cycling reliability study of ultrasonically bonded copper wires - Arjmand, Elaheh; Agyakwa, Pearl A.; Corfield, Martin R.; Li, Jianfeng; Mouawad, Bassem; Mark Johnson, C. (Elsevier, 2016)
In this work we report on a reliability investigation regarding heavy copper wires ultrasonically bonded onto active braze copper substrates. The results obtained from both a non-destructive approach using 3D X-ray tomography and shear tests showed no discernible degradation or wear out from initial conditions to 2900 passive thermal cycles from − 55 to 125 °C. Instead, an apparent increase in shear strength is observed as the number of thermal cycles increases. Nanoindentation hardness investigations suggest the occurrence of cyclic hardening. Microstructural investigations of the interfacial morphologies before and after cycling and after shear testing are also presented and discussed.